2018
DOI: 10.7150/ijbs.26111
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Elastase Inhibitors and Chronic Kidney Disease

Abstract: End-stage renal disease (ESRD), the last stage of chronic kidney disease (CKD), is characterized by chronic inflammation and oxidative stress. Neutrophils are the front line cells that mediate an inflammatory response against microorganisms as they can migrate, produce reactive oxygen species (ROS), secrete neutrophil serine proteases (NSPs), and release neutrophil extracellular traps (NETs). Serine proteases inhibitors regulate the activity of serine proteases and reduce neutrophil accumulation at inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 170 publications
(302 reference statements)
0
61
0
Order By: Relevance
“…On the one hand, neutrophils promote tissue repair through phagocytosis and activation of the immune response. Conversely, neutrophils may cause tissue damage through the release of proteolytic enzymes and reactive oxygen metabolites . Furthermore, activated neutrophils contribute to the development of interstitial edema through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, neutrophils promote tissue repair through phagocytosis and activation of the immune response. Conversely, neutrophils may cause tissue damage through the release of proteolytic enzymes and reactive oxygen metabolites . Furthermore, activated neutrophils contribute to the development of interstitial edema through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, neutrophils may cause tissue damage through the release of proteolytic enzymes and reactive oxygen metabolites. 71,[73][74][75] Furthermore, activated neutrophils contribute to the development of interstitial edema through different mechanisms. First, adhesion of neutrophils to the endothelial cell wall (leukocyte plugging) reduces the diameter of the postcapillary venules, which results in an increase in hydrostatic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The similar inhibitory tendency was also observed from other alkylated flavones 3 and 4, which indicated that the prenyl group on C3 was a crucial functionality to HNE inhibition. Dihydrobenzoxanthones (5)(6)(7)(8) inhibited HNE significantly with IC 50 values of 9.8 ~ 28.7 μM, compared to the mother compound. The number of the hydroxyl group of B-ring affected inhibitory capacities as follow: compounds 5 (IC 50 = 9.8 μM) versus 8 (IC 50 = 28.7 μM).…”
Section: Hne Inhibitory Activity Of Isolated Compounds and Their Kinementioning
confidence: 96%
“…Augmentation therapy has been accepted as the best therapy for AAT deficiency, and less costly methods such as low molecular weight NE inhibitors have failed clinically, despite diligent efforts over the past three decades [6]. On the other hand, the release of granular contents leads to the recruitment of inflammatory cells through cytokines (TNF-α, IL-1β, IL-6, IL-18, IL-10), adipokines (adiponectin, resistin and leptin), and chemokines (IL-8), which are the main intermediaries and progressors of renal tissue damage [7]. Thus, the invention of novel protease inhibitors is an invaluable therapeutic tool.…”
Section: Introductionmentioning
confidence: 99%
“…HNE and other serine proteases are key enzymes involved in inflammation, coagulation, and host defense (Massberg et al, ; Pham, ). On the other hand, HNE also plays a central role in several inflammatory diseases, such as chronic obstructive pulmonary disease (Lucas, Costa, Guedes, & Moreira, ; Pandey, De, & Mishra, ), cystic fibrosis (Twigg et al, ), rheumatoid arthritis (Hilbert, Schiller, Arnhold, & Arnold, ), cancer (Akizuki et al, ; Lerman et al, ; Lerman & Hammes, ; Vaguliene, Zemaitis, Lavinskiene, Miliauskas, & Sakalauskas, ), and other disorders with an inflammatory component (Bronze‐da‐Rocha & Santos‐Silva, ; Marto et al, ). Because of their potential for proteolytic tissue damage, neutrophil protease activity is regulated by specific endogenous (α‐1 antitrypsin, secretory leucocyte protease inhibitor and elafin) and exogenous inhibitors, thereby preventing several inflammatory diseases with severe impact on organ tissue integrity (von Nussbaum et al, ; von Nussbaum & Li, ).…”
Section: Introductionmentioning
confidence: 99%